Pharmacological treatments and medication-related problems in nursing homes in Catalonia: a multidisciplinary approach - Emilie Anderssen-Nordahl; Emilie Anderssen-Nordahl; Emilie Anderssen-Nordahl; Margarita Sánchez-Arcilla Rosanas; Montserrat Bosch Ferrer; Montserrat Bosch Ferrer; Montserrat Bosch Ferrer; Mònica Sabaté Gallego; Mònica Sabaté Gallego; Mònica Sabaté Gallego; Eladio Fernández-Liz; Eladio Fernández-Liz; et al. (Frontiers Media S.A., 2024)
Background: Aging correlates with increased frailty, multi-morbidity, and chronic diseases. Furthermore, treating the aged often entails polypharmacy to achieve optimal disease management, augmenting medication-related problems (MRPs). Few guidelines and tools address the problem of polypharmacy and MRPs, mainly within the institutionalized elderly population. Routine pharmacological review is needed among institutionalized patients. This pharmacological review may improve with a multidisciplinary approach of a collaboration of multiple health professionals. This study aimed to describe institutionalized patients, systematically review their medication plans, and then give recommendations and identify MRPs.Methods: A cross-sectional study was performed using data obtained from patients living in five nursing homes in the northern area of Barcelona, Spain. The inclusion criteria comprised institutionalized patients with public health coverage provided by the Health Department of Catalonia. A detailed description of the clinical characteristics, chronic diseases, pharmacological treatments, recommendations, incomplete data, and MRPs, such as potential drug-drug interactions, therapeutic duplications, contraindications, and drugs deemed inappropriate or of doubtful efficacy, was made. The clinical pharmacologist was the medical doctor specialist who acted as the coordinator of the multidisciplinary team and actively reviewed all the prescribed medications to make recommendations and detect MRPs.Results: A total of 483 patients were included. Patients had a mean age of 86.3 (SD 8.8) years, and 72.0% were female individuals. All patients had at least three health-related problems, with a mean of 17.4 (SD 5.6). All patients, except one, had a minimum of one prescription, with a mean of 8.22 drugs prescribed (SD 3.5) per patient. Recommendations were made for 82.4% of the patients. Of these recommendations, verification of adequate use was made for 69.3% and withdrawal of a drug for 49.5%.Conclusion: This study demonstrates a high prevalence of health-related problems and several prescribed drugs in nursing homes in Catalonia. Many recommendations were made, confirming the increased proportion of polypharmacy, MRPs, and the need for standardized interventions. A multidisciplinary team approach, including general practitioners, geriatric assessments, a clinical pharmacist, and a clinical pharmacologist, should address this problem.